Survival following intentional massive overdose of 'Ecstasy'. Issue 1 (March 1994) - Roberts, L; Wright, H
Abstract : A case of intentional overdose with 18 'Ecstasy' tablets is described. 'Ecstasy' is a semi-synthetic hallucinogenic amphetamine and acute adverse reactions follow from the effects of sympathetic stimulation. To our knowledge this is the first reported case of massive intentional overdose reported in the literature.